Assessment of visual sensation, psychiatric profile and quality of life following vestibular schwannoma surgery in patients prehabituated by chemical vestibular ablation - Balatková, Zuzana; Čada, Zdeněk; Hrubá, Silvie; Komarc, Martin; Černý, Rudolf (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2020)
AIMS: Preoperative chemical vestibular ablation can reduce vestibular symptoms in patients who have gone through vestibular schwannoma resection. The goal of this study was to determine whether chemical vestibular prehabituation influences the patients' post-operative perception of visual stimulation, mental status and quality of life. We also tried to find out whether increases of optokinetic nystagmus, measured by routine electronystagmography, correlate with subjective symptoms. METHODS: We preoperatively administered (2 months prior to surgery) 0.5 - 1.0 mL of 40 mg/mL nonbuffered gentamicin in three intratympanic instillations in 11 patients. Head impulse and caloric tests confirmed reduction of vestibular function in all patients. The control group consisted of 21 patients. Quality of life in both groups was evaluated using the Glasgow Benefit Inventory, the Glasgow Health Status Inventory and the Dizziness Handicap Inventory questionnaires. Visual symptoms and optokinetic sensation were evaluated using a specific questionnaire developed by our team and by measuring gains preoperatively and postoperatively in both groups using routine electronystagmography. The psychological profile was evaluated using the Zung Self-Rating Depression Scale and the Generalised Anxiety Disorder Assessment questionnaires. RESULTS: There were no statistically significant differences between both groups with regards to the results of the questionnaires. Patients who received preoperative gentamicin were less sensitive to visual stimulation (P<0.10) and many of them had a significantly higher gain in the optokinetic nystagmus than the control group in the preoperative stage. CONCLUSION: Pre-treatment with gentamicin helps to lower anxiety levels in patients and improves their general postoperative status. Pre-treated patients are also less sensitive to optokinetic stimulation. TRIAL REGISTRATION: ClinicalTrials.gov, NCT03638310.
Keywords: Young Adult; Postoperative Period; vestibulární schwannom; Vestibule, Labyrinth; Male; kvalita života; zraková ostrost; Quality of Life; Gentamicins; mladý dospělý; antibakteriální látky; Adult; vestibulární aparát; Aged; dospělí; gentamiciny; mužské pohlaví; senioři; čití, cítění; průzkumy a dotazníky; Visual Acuity; pooperační období; předoperační péče; lidé; ženské pohlaví; Anti-Bacterial Agents; Humans; Female; Neuroma, Acoustic; Preoperative Care; Surveys and Questionnaires; lidé středního věku; Sensation; Middle Aged